Fascist Hybridities Representations of Racial Mixing and Diaspora Cultures under Mussolini - Caponetto, Rosetta Giuliani. (Italian and Italian American Studies, 2015)
Under Italian Fascism, African-Italian mulattoes and white Italians living in Egypt posed a particular threat to the pursuit of a homogenous national identity. This book examines novels and films of the period, showing that their attempts at stigmatization were self-undermining, forcing audiences to reassess their collective identity.